2018
DOI: 10.5021/ad.2018.30.6.688
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Evaluate the Efficacy and Safety of Treatment with Botulinum Toxin in Patients with Recalcitrant and Persistent Erythematotelangiectatic Rosacea

Abstract: Background: There are few pharmacologic options to reduce erythema and flushing in patients with recalcitrant erythematotelangiectatic rosacea (ETR). We previously reported two cases of refractory flushing and erythema of rosacea that were successfully treated with intradermal botulinum toxin injection, and additional research is needed to prove the efficacy and safety of this treatment. Objective: To report the efficacy and safety of botulinum toxin injection as an aid in persistent erythema of rosacea patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 23 publications
1
33
0
2
Order By: Relevance
“…They did not follow up possibly due to the dissatisfaction of treatment effects, or potential concern about adverse effects. In Park et al study, 31 facial muscle paralysis was reported in three patients, and resolved without any special treatment. This was possibly due to treatment volume and injection depth.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…They did not follow up possibly due to the dissatisfaction of treatment effects, or potential concern about adverse effects. In Park et al study, 31 facial muscle paralysis was reported in three patients, and resolved without any special treatment. This was possibly due to treatment volume and injection depth.…”
Section: Discussionmentioning
confidence: 88%
“…In Bloom et al study with 25 participants, 28 one withdrew, and nine had inconsistent follow-up visits, the reason for which was not provided. In Park et al study with 20 Korean patients, 31 three patients reported undesired paralysis of facial muscles and stopped participating the study, although their symptoms were resolved without any special treatment. In Kim et al study with 24 participants, 33 one patient was excluded because of protocol violation, intake of muscle relaxant for ankle sprain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations